Prevalence, risk factors, and prediction of inappropriate use of non-vitamin K antagonist oral anticoagulants in elderly Chinese patients with atrial fibrillation: A study protocol - Zhao, Shu-Juan; Chen, Bo-Ya; Hong, Xue-Jiao; Liu, Yin-Ping; Cai, Hai-Xia; Du, Song; Gu, Zhi-Chun; Ma, Pei-Zhi (Frontiers in Cardiovascular Medicine, 2022)
Background: Atrial fibrillation (AF) is an arrhythmia that is prevalent globally, and its incidence grows exponentially with aging. Non-vitamin K antagonist oral anticoagulants (NOACs) have been developed in the recent past and challenge the supremacy of warfarin for thromboembolism prophylaxis in AF. Nevertheless, there are limited data specifically evaluating the real-life use of NOACs in elderly AF patients in China. Methods: This is a national, multicenter, non-interventional, cross-sectional study that enroll patients with AF aged 75 years and above from 31 institutions across China. Data were collected via the Hospital Information System. The primary outcomes include: (1) profiles of NOAC use in the elderly; (2) frequency of inappropriate NOAC use based on guidelines and approved labeling recommendations; (3) exploring potential risk factors related to NOACs inappropriate use; (4) creating prediction tool for inappropriate NOACs use. Conclusions: The results of this study will unveil the prevalence, risk factors, and corresponding prediction tool of inappropriate NOACs use in older patients with AF in China, as well as provide valuable insights into the clinical application of NOACs in high-risk populations in the real-world setting. (This study was registered at ClinicalTrials.gov (NCT 05361889)